2009
DOI: 10.1371/journal.pone.0006251
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Facilitates the Development of Breast Cancer Resistance to the Anti-HER2 Monoclonal Antibody Trastuzumab

Abstract: Autophagy has been emerging as a novel cytoprotective mechanism to increase tumor cell survival under conditions of metabolic stress and hypoxia as well as to escape chemotherapy-induced cell death. To elucidate whether autophagy might also protect cancer cells from the growth inhibitory effects of targeted therapies, we evaluated the autophagic status of preclinical breast cancer models exhibiting auto-acquired resistance to the anti-HER2 monoclonal antibody trastuzumab (Tzb). We first examined the basal auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
204
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 218 publications
(224 citation statements)
references
References 78 publications
15
204
1
Order By: Relevance
“…These results indicated that autophagy caused by targeting AURKA contributed to breast cancer cells resistance to VX-680. Similar studies, consistent with these findings, show that activated autophagy can protect tumor cells from targeted therapies, such as trastuzumab in breast cancer, 44 the imatinib mesylate in Philadelphia chromosome-positive cells, 45 and proteasome inhibitors in prostate cancer. 46 Thus, our data, along with these reports, supported that autophagy might contribute to a drug-resistance mechanism.…”
Section: Discussionsupporting
confidence: 81%
“…These results indicated that autophagy caused by targeting AURKA contributed to breast cancer cells resistance to VX-680. Similar studies, consistent with these findings, show that activated autophagy can protect tumor cells from targeted therapies, such as trastuzumab in breast cancer, 44 the imatinib mesylate in Philadelphia chromosome-positive cells, 45 and proteasome inhibitors in prostate cancer. 46 Thus, our data, along with these reports, supported that autophagy might contribute to a drug-resistance mechanism.…”
Section: Discussionsupporting
confidence: 81%
“…The induction of autophagy is closely related to the cell survival triggered by ErbB2 gene-amplified human breast cancer cells in response to the anti-ErbB2 monoclonal antibody, trastuzumab (30). Knockdown of autophagy genes in combination with tamoxifen in tamoxifen-resistant ErbB2-overexpressing MCF7 cells, reduced cell viability with increased mitochondria-mediated apoptosis (29).…”
Section: Discussionmentioning
confidence: 99%
“…17,18 A series of studies reported that chemotherapy induced-autophagy promotes the survival of some kinds of cancer cell lines. [19][20][21][22][23] These results suggest that autophagy might be involved in the development of chemotherapy resistance.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%